UJI CEMARAN BAKTERI Escherichia coli DANColiform PADA SUSU KEDELAI YANG DI JUAL DIWARUNG KAWASAN KELURAHAN SUKAJADI KECAMATAN SUKAJADI PEKANBAR - Izzatul Mey thri Aria (Jurnal Penelitian Farmasi Indonesia)
Test contamination of E.coli and Coliform bacteria in soybean milk sold in Sukajadi Village area Sukajadi District Pekanbaru City. This study aims to determine the existence of contamination and the number of E. coli and coliform bacteria in soy milk milk sold in the stalls Sukajadi District Sukajadi District Pekanbaru City by using the method of ALT and MPN method. Soy milk samples were obtained from five stalls with different producers, namely Sample A, B, C, D and E. Based on the conclusions of the research results for quality requirements of soy milk according to SNI No 01-3830 of 1995 that soy milk sold in stalls of Sukajadi Village area Sukajadi District Pekanbaru City is polluted by bacteria. With MPN value for E.coli bacteria> 3 APM / 100ml, and for bacterium Coliform> 20 APM / 100ml. The results for ALT values ​​exceeded the threshold of 2 x 102 colonies / ml. Good soy milk is consumed at least three days after preparation.